2003
DOI: 10.1017/s1355617703930074
|View full text |Cite
|
Sign up to set email alerts
|

The effects of practice on the cognitive test performance of neurologically normal individuals assessed at brief test–retest intervals

Abstract: Performance on many cognitive and neuropsychological tests may be improved by prior exposure to testing stimuli and procedures. These beneficial practice effects can have a significant impact on test performance when conventional neuropsychological tests are administered at test-retest intervals of weeks, months or years. Many recent investigations have sought to determine changes in cognitive function over periods of minutes or hours (e.g., before and after anesthesia) using computerized tests. However, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
270
5
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(300 citation statements)
references
References 19 publications
13
270
5
5
Order By: Relevance
“…For example, the study by Shiroma et al (2014) found that impaired attention, but not impaired processing speed per se, was associated with improved antidepressant response to ketamine. This discrepancy could be, in part, due to the differences in neurocognitive assessments utilized (the MCCB was utilized in the current study, compared with the CogState battery (Collie et al, 2003) in the study by Shiroma et al (2014)). The current study examined neurocognitive function using a comprehensive battery, but optimal biomarker assessments will likely require multi-modal data acquisition, potentially including neuroimaging (Zarate et al, 2013), quantitative electroencephalography (qEEG) (Cook et al, 2013), and peripheral blood markers (Uddin, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…For example, the study by Shiroma et al (2014) found that impaired attention, but not impaired processing speed per se, was associated with improved antidepressant response to ketamine. This discrepancy could be, in part, due to the differences in neurocognitive assessments utilized (the MCCB was utilized in the current study, compared with the CogState battery (Collie et al, 2003) in the study by Shiroma et al (2014)). The current study examined neurocognitive function using a comprehensive battery, but optimal biomarker assessments will likely require multi-modal data acquisition, potentially including neuroimaging (Zarate et al, 2013), quantitative electroencephalography (qEEG) (Cook et al, 2013), and peripheral blood markers (Uddin, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…33,34 At least several of the tests used in our battery (i.e., Trail's test, Finger Tapping test, Digit Span forward, Reaction time) have been reported to lack significant practice effects. 35 To minimize potential practice effects in the current study, tests with alternate forms were selected whenever possible (e.g., 4 forms of the Selective reminding test) and the tests were administered in a predetermined order.…”
Section: Discussionmentioning
confidence: 99%
“…All participants (training group and control group) were tested twice, before the intervention group received the intervention. This 'dual baseline procedure' was used in order to reduce practice and procedure-learning effects [37]. The mean interval between measurements 1 and 2 was 17 days (S.D.…”
Section: Methodsmentioning
confidence: 99%